THE EFFECTIVENESS OF MODERN STUDENT-CENTERED STRATEGIES IN LANGUAGE LEARNING CLASSROOMS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study explores the effectiveness of modern student-centered strategies in language learning classrooms and their impact on students’ academic achievement, motivation, and classroom engagement. Student-centered approaches encourage active participation, collaboration, critical thinking, and independent learning, making the educational process more interactive and meaningful. The research highlights various modern teaching methods such as collaborative learning, problem-based learning, project-based learning, and technology-assisted instruction. The findings suggest that these approaches improve learners’ communication skills, increase motivation, and create a positive learning environment. Furthermore, student-centered strategies help teachers address individual learning needs and develop learners’ confidence and autonomy. The study concludes that integrating modern student-centered methods into language education significantly enhances the quality and effectiveness of the teaching and learning process.